Long-Term Care Services for the Elderly : Background Materials on Financing and Delivery of Long-Term Care Services for the Elderly. (U.S. Congressional Research., 1986)
CRS report, prepared by Jeanne E. Griffith, et al. for the Subcom on Health and the Environment, examining long-term health care delivery and financing policy issues.